Examining Chefs' Social Responsibility (CSR) during the COVID-19 pandemic. Issue 3 (3rd July 2022) - De Guzman, Allan B.; Mesana, John Christopher B.; Roman, Jonas Airon M.
ABSTRACT: Anchored on Dowling and Pfeffer's (1975) Legitimacy Theory, this thematic content analysis paper purports to understand the ontology of various social responsibility-driven initiatives of chefs in various countries. Specifically, YouTube videos and online news published by major search engines were content analysed. Interestingly, a concept dubbed as The Anatomy of a Caring Chef during the COVID-19 Pandemic, consisting of three constructs of chefs as the Community Supporter, Community Leverager, and Community Enabler, emerged that offers an interesting portrait of global chefs' corporate social responsibility in this challenging times. The implications of the study's findings to the food industry, limitations, and recommendations were also discussed.